Optimal pricing and trade-in remanufacturing policies considering the secondary market. Issue 4 (2nd October 2021) - Wu, Lu; Guo, Qiang; Li, Fuchang
Abstract: As global environmental problems worsen, issues related to the closed-loop supply chain and trade-in program have gained wide attention. We construct a dual-market model to explore trade-in program and remanufacturing strategies under two scenarios: original equipment manufacturer (OEM) recycling and retailer recycling. We find that under single market strategies, OEM recycling consumers benefit more with the reduction of new product costs. Interestingly, the opposite is true under dual-market strategies with an increase in consumers' maximum willingness to pay in the secondary market. Optimal choices regarding trade-in program strategies and remanufacturing strategies depend on different value ranges of consumers' maximum willingness to pay in the secondary market, and the cost of the new product.